2019
DOI: 10.1016/j.jccase.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A case of thrombolytic therapy with recombinant tissue plasminogen activator for mechanical valve thrombosis at 9 weeks of pregnancy in a Japanese woman

Abstract: A 29-year-old woman was admitted to our hospital due to diagnosis of pregnancy at 5 weeks and a day. She underwent valve replacement with mechanical heart valve (MHV: SJM valve) for congenital mitral valve regurgitation, when 11 years old. Warfarin 4 mg was used for anticoagulation. After admission, warfarin was replaced by unfractionated heparin (UFH). She developed exertional dyspnea at 8 weeks of pregnancy. Echocardiogram and fluoroscopy showed an immobile leaflet in the closed position. She was diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…We are thankful for your insightful and thorough comment on our article [1]. In particular, we completely agree with your concern regarding the optimal anticoagulation strategy in the first trimester of pregnancy.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…We are thankful for your insightful and thorough comment on our article [1]. In particular, we completely agree with your concern regarding the optimal anticoagulation strategy in the first trimester of pregnancy.…”
mentioning
confidence: 54%
“…
Letter to the Editor Author's reply to "Anticoagulation strategy and management of patients with mechanical prosthetic heart valves during pregnancy"We are thankful for your insightful and thorough comment on our article [1]. In particular, we completely agree with your concern regarding the optimal anticoagulation strategy in the first trimester of pregnancy.
…”
mentioning
confidence: 79%
“…For the reasons described above, European Society of Cardiology/European Association for Cardiothoracic Surgery guidelines regarding the management of cardiovascular diseases during pregnancy recommend the use of low-dose warfarin in women who are able to maintain therapeutic international normalized ratios (Class IIa) over the use of either low molecular weight heparin or UFH in the first trimester (Class IIb) [3]. In the present case reported by Komatsu et al [1], it was debatable that UFH was used as anticoagulation therapy in the first trimester in a patient needing low-dose warfarin (4 mg/day) for anticoagulation. Furthermore, continuous intravenous infusion made the patient prone to additional risks such as catheter-associated bacteremia.…”
mentioning
confidence: 68%
“…We have read with great interest the article by Komatsu et al entitled "A case of thrombolytic therapy with recombinant tissue plasminogen activator for mechanical valve thrombosis at 9 weeks of pregnancy in a Japanese woman" [1]. The authors have reported the management of a pregnant patient with mechanical prosthetic valve thrombosis in mitral position.…”
mentioning
confidence: 99%